Towards a big data solution for analyzing the reputational impact of the Tennis Italian Open - Oro, E.; Ruffolo, M. (Proceedings of the KDD-16 Workshop on Large-Scale Sports Analytics, 2016)
The Italian Open is part of the nine main tennis tournaments in the world after those of the Grand Slam. This event has grown over the years generating value, not only for the event itself, but also for social and economic context in which it is grafted, and in particular to the city of Rome that annually hosts it. In this paper we present the initial results of an analysis that aims at evaluating the impact of the Italian Open by measuring its reputation on the web. To get our goal we exploit a Big Data Analytics platform that enables to: (i) extract contents from heterogeneous sources, (ii) perform text analysis, and (iii) visualize results. In particular, we carry out a quantitative and qualitative analysis of texts related to the event coming from social networks and newspapers. The work is a step forward in the analysis of these kind of tennis events not considered until now, and an advancement towards the definition of a shared method to process online resources about sports events.